A Prospective Study To Evaluate Medical Management Vs Surgical Intervention In Pain Relief And Healing Of Anal Fissure (Journal of Society of Surgeons of Nepal, 2023)
Introduction: Anal fissure is a commonly encountered problem for surgeons. It is a longitudinal tear in distal anal canal with or without an ulcer. It causes significant changes in quality of life. This study was done to compare the efficacy of medical management and surgical intervention in cases of anal fissures.Methods: 50 patients were divided into two groups of 25 each. Group A patients were treated with topical application of 2% diltiazem gel and Group B patients were treated with Lateral sphincterotomy. Both groups were examined weekly for 4 weeks for pain using VAS score and at 12 weeks for healing.Results: 21(84%) patients were pain free after 4 weeks under Group A, 24 (96%) patients were pain free after 4 weeks under Group B. 22(88%) patients were completely healed at 12 weeks under Group A, 25(100%) patients were completely healed at 12 weeks under Group B.Conclusion: Lateral sphincterotomy can be advocated as treatment of choice for anal fissures. It has better pain relief and healing rates compared to topical application of 2% diltiazem gel. Medical Management can be used in patients refusing surgery or unfit for surgery